Sustainable Tourists Behaviour on Environmental Aspects in Pangandaran Beach - Hilman Khaerul Nizar; Gundur Leo (Journal of Tourism Sustainability, 2023)
This study aims to determine how the level of tourist behavior in environmental aspects of sustainable tourism activities and is useful for reducing the negative impact of environmental pollution on Pangandaran Beach by adjusting actions that need to be taken in the future. This study uses a descriptive quantitative method through a questionnaire with the contents of the questionnaire consisting of the realm of knowledge (knowledge), the realm of attitude (attitude), and the realm of action or (practice) which have been tested for validation and reliability of 30 respondents. Then the research sources used in this study are primary data and secondary data. Research respondents were 100 tourists who visited Pangandaran Beach from 2020 to 2022. Based on the results of the study, it was found that all sub-variables were in the high category on the continuum line, but this is contrary to the phenomenon that occurred on Pangandaran Beach, there are still many tourists who litter. However, tourists feel that sustainable tourism activities are important to do so as not to have a negative impact on the environment on Pangandaran Beach. The sub-variable that has the highest average score is the knowledge sub-variable so that it can be interpreted that tourists' knowledge about sustainable tourism is higher than attitudes and actions, especially in the action sub-variable which is the sub-variable with the lowest score which can be caused by several factors. factors such as education or age.